Types of episodic disability among people living with HIV in Zambia. Issue 10 (2nd October 2020) - Solomon, Patricia; Bond, Virginia; Cameron, Cathy; Menon, J. Anitha; Maimbolwa, Margaret C.; Nixon, Stephanie A.
ABSTRACT: HIV is increasingly recognized as a chronic illness which may result in episodic disability related to the effects of the virus, side effects of medication, co-morbidities and consequences of aging. Little is known about the episodic disability experiences of people living long-term with HIV in resource-limited countries, which is best understood by following people over time. This qualitative longitudinal study examined the episodic disability experiences and the applicability of four types of episodic disability among people living with HIV and on anti-retroviral therapy in Zambia. We interviewed 31 men and women living with HIV on 3 occasions at 6-month intervals (total of 93 interviews) examining the processes of change over time. We used disability models to inform the interviews exploring impairments/symptoms, activity limitations and participation restrictions. Longitudinal analyses of transcribed interviews confirmed the applicability of four types over time: stable, increasing disability, decreasing disability and significant fluctuations. Analyses highlighted the extent to which determinants of health contributed to the disability experienced. The use of disability models revealed the importance of environmental and social influences on disability and quality of life. The indicators of the type of episodic disability could be used clinically to help understand the nature and potential triggers of the episodes.